Personality Traits as Predictors of Affective Styles among Young People - Davidović Rakić, Jelena I.; Pavićević, Miljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The focus of this paper is the understanding of personality trait prediction in anticipating a particular affective style among young people. The sample consists of 171 students from University of Priština in Kosovska Mitrovica, of both genders, aged 18–26. The data have been processed using descriptive statistics, correlation and regression analysis, and t-test. The most dominant dimension of personality is agreeableness, and the most dominant dimension of affective styles is adjusting. The prediction of personality dimensions in predicting a certain affective style has been confirmed, so that neuroticism is essential in the prediction of all three affective styles. In the prediction of affective style of concealing, personality traits as a model explain 10.7% variance, and besides neuroticism (β = -298; p <0.01), the contribution has been given by extraversion, as well (β = -221, p <0.05). The personality traits explain 36.1% of the variance of adjusting, and the unique contribution has been given by neuroticism (β = -.596, p <0.01), while in the prediction of affective style of tolerating, personality traits explain 9.8% of the total variance, with a significant predictor – neuroticism (β = -.241, p <0.05). Gender has not proven to be a significant source of differences in the expression of affective styles, while there are gender differences in the expression of extraversion and agreeableness in favour of female respondents.